2014
DOI: 10.1038/srep03829
|View full text |Cite
|
Sign up to set email alerts
|

Rapid recovery of soil bacterial communities after wildfire in a Chinese boreal forest

Abstract: Fires affect hundreds of millions of hectares annually. Above-ground community composition and diversity after fire have been studied extensively, but effects of fire on soil bacterial communities remain largely unexamined despite the central role of bacteria in ecosystem recovery and functioning. We investigated responses of bacterial community to forest fire in the Greater Khingan Mountains, China, using tagged pyrosequencing. Fire altered soil bacterial community composition substantially and high-intensity… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

24
119
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 132 publications
(152 citation statements)
references
References 46 publications
24
119
0
Order By: Relevance
“…However, we found this effect was absent in burnt stands, indicating that fire may disrupt plantmicrobial feedbacks. Indeed, fire can influence both arbuscular mycorrhizal fungi and bacterial community composition, with effects lasting at least a year (Xiang et al 2014(Xiang et al , 2015. As most seedling recruitment in eucalypt forests occurs following fire (Gill 1997), this positive feedback effect may not be important during the early establishment of E. globulus seedlings in the wild, but could be during later growth.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…However, we found this effect was absent in burnt stands, indicating that fire may disrupt plantmicrobial feedbacks. Indeed, fire can influence both arbuscular mycorrhizal fungi and bacterial community composition, with effects lasting at least a year (Xiang et al 2014(Xiang et al , 2015. As most seedling recruitment in eucalypt forests occurs following fire (Gill 1997), this positive feedback effect may not be important during the early establishment of E. globulus seedlings in the wild, but could be during later growth.…”
Section: Discussionmentioning
confidence: 99%
“…While fire is generally known to impact soil communities (e.g., Dooley and Treseder 2012;Xiang et al 2014Xiang et al , 2015, to our knowledge, we are the first to investigate the influence of forest fire on plantmicrobial feedbacks. A well-documented consequence of fire in eucalypt forest is the 'ashbed effect' (Humphreys and Lambert 1965;Loneragan and Loneragan 1964;Pryor 1963), where the germination and performance of eucalypt seedlings are enhanced following fire, particularly seedlings of species belonging to the ash group (subgenus Eucalyptus, series Obliquae; Ashton and Attiwill 1994;Neyland et al 2009), which includes E. obliqua.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Previous studies have shown how wildfire reduces belowground microbial biomass (Stendell et al 1999;Vernes et al 2004;Wang et al 2012), mycorrhizal fungal rootcolonization (Buchholz and Motto 1981), and bacterial diversity (Ferrenberg et al 2013). Similar to the aboveground community, microbial community composition is altered by fire (Xiang et al 2014). The impact of fire on microbial biomass has been shown to persist for years (Isobe et al 2009;Guénon et al 2011).…”
Section: Introductionmentioning
confidence: 97%
“…Despite a substantial body of work on how wildfire significantly alters soil bacterial and saprobic fungal communities, showing that the recovery of these communities can require multiple years (Hart et al 2005;Cairney and Bastias 2007;Hamman et al 2007;Xiang et al 2014), there is a dearth of information on how arbuscular mycorrhizal fungal (AMF) communities are shaped by wildfire. AMF are obligate biotrophs that form mutualistic symbioses with more than 80 % of land plants, providing their hosts with nutrients in exchange for photosynthate (van der Heijden et al 1998;Moora et al 2004).…”
Section: Introductionmentioning
confidence: 99%